PENYULUHAN DAN PEMBUATAN PUPUK ORGANIK DI DUSUN DUNGTILENG DESA SOMONGARI, KECAMATAN KALIGESING, KABUPATEN PURWOREJO, PROVINSI JAWA TENGAH - Mahrus Ali (Asian Journal of Innovation and Entrepreneurship, 2015)
Farmers in dusun Dungtileng, Somongari village, district of Kaligesing, Purworejoregency, Central Java Provisions, had used organic’s fertilizer. But, they still used thebasic material, so the quality is still low. This program was conducted to provideadditional insights and teach the farmers of this village cultivate organic fertilizerscomposed of animal waste, dry leaves, green leaves, fruits decanter of waste, and soil. Byimproved the quality of organic’s fertilizer, farmers would get many benefits.